GeneXpert: a game changer in the detection and diagnosis of childhood tuberculosis - Gandra, Nayantara Rao; Gali, Jayasri Helen (International Journal of Contemporary Pediatrics, 2017)
Background: Battling against tuberculosis (TB) is still a major challenge in India, despite measures undertaken by the government and medical fraternity. Delay in diagnosing tuberculosis is a challenge, causing hurdle in the prevention of spread of the disease. Methods: This retrospective study analysed the samples by geneXpert assay. Samples (n=403, from 359 children) included pulmonary (sputum and gastric aspirate, 359), extrapulmonary (lymph node aspirate (LNA), 41) cerebrospinal fluid (CSF, 03) pus from the lesion at the elbow joint (01). Only sputum was analysed for 315 children, both sputum and LNA for 41. Results: Mean age of patients was 9.08±2.85 years, range 3-15 years. There were 221 (61.56%) males and 138 (38.44%) females. Fever (71, 19.78%), fever with cough (87, 24.23%), fever with weight loss (41,11.42%) were the main symptoms. There were three patients with high fever, headache and seizures with neck rigidity, clinically diagnosed as Tuberculous meningitis. There was history of contact with Tuberculosis in 15 (4.18%) patients. Mean ESR was 112.09mm/1st Hr±56.05 (range 54 -750 mm/1st Hr). Mantoux test was positive in 270 (75.42%). Chest X-ray was normal in 33 (9.19%); consolidation in 189 (52.65%), mild pleural effusion in 94 (26.18%) mild pleural effusion associated with consolidation in 43 (11.98%) were reported. Positive GeneXpert assay (106 samples, 27.39%; sputum (87, 24.23% %), pus (01), CSF (03), LNA (15, 57.69%) was reported in 87 patients. Results were obtained ≤36 hours, mean 2 hours± 2.34 (range 6- 36 hours). Conclusions: GeneXpert is an effective tool for rapid detection of tuberculosis. Present study supports its inclusion in the battery of routine investigations. It can revolutionise the scenario in prevention and management of tuberculosis.